Engineering strategies for allogeneic solid tissue acceptance - Sousa, Ana Rita (2022)
Systemic immunosuppressants have allowed the transplantation of life-saving organs. However, they cause deleterious effects and long-term graft failure. Strategies promoting allogeneic graft acceptance and the maintenance of immunological competence have been proposed. Cell-based tolerance-inducing strategies that preserve immune competence have already extended human allograft acceptance, although toxic side effects or difficult reproduction of observed effects in humans have counteracted their clinical translation. Localized tolerance/immunosuppression mediated through bioengineered setups comprising immunomodulatory biomaterials and/or tissue engineering-inspired tools already achieved allograft acceptance in murine models and are game changing in the field. Such advances have contributed to unveiling the complex interplay of immune cells and allogeneic transplants. Advances in allogeneic transplantation of solid organs and tissues depend on our understanding of mechanisms that mediate the prevention of graft rejection. For the past decades, clinical practice has established guidelines to prevent allograft rejection, which mostly rely on the intake of nontargeted immunosuppressants as the gold standard. However, such lifelong regimens have been reported to trigger severe morbidities and commonly fail in preventing late allograft loss. In this review, the biology of allogeneic rejection and self-tolerance is analyzed, as well as the mechanisms of cellular-based therapeutics driving suppression and/or tolerance. Bioinspired engineering strategies that take advantage of cells, biomaterials, or combinations thereof to prevent allograft rejection are addressed, as well as biological mechanisms that drive their efficacy.